Implementasi model pembelajaran project based learning berbasis STEM sebagai upaya meningkatkan kemampuan literasi matematika - Abdul Rahman; Asdar Dollo; Eliyawati Eliyawati; Miftahul Jannah (PYTHAGORAS : Jurnal Program Studi Pendidikan Matematika, 2026)
This research is intended to increase students' mathematical literacy by implementing a STEM-based Project Based Learning model. Research activities were carried out in two cycles with a total of 10 meetings, consisting of 8 learning activities and 2 mathematical literacy tests. The mathematical literacy indicators measured include communication skills, representation, mathematization, and strategy selection. The subjects of this research were 27 students of class XI Excellent D at SMA Negeri 2 Parepare. Research data was collected using mathematical literacy tests and student observation sheets. Funds are analyzed using SPSS. After the implementation of cycle II, the average student mathematics literacy score reached 70.12 (medium category), indicating an improvement from cycle I which only reached 52.10 (low category). This improvement is also shown by a decrease in the standard deviation from 26.54 to 19.33, which indicates that student achievement is more even. The distribution of ability categories also experienced a shift, where the proportion of students in the low category decreased and the high category increased. There was an increase in student activity in almost the observed indicators, with the note that the mathematical communication aspect is still an area that requires improvement. Thus, the implementation of STEM-based PjBL has proven to be effective in increasing mathematical literacy while encouraging equal distribution of student learning outcomes.